2015
DOI: 10.4236/jsea.2015.82007
|View full text |Cite
|
Sign up to set email alerts
|

Content-Based Image Retrieval Using SOM and DWT

Abstract: Content-Based Image Retrieval (CBIR) from a large database is becoming a necessity for many applications such as medical imaging, Geographic Information Systems (GIS), space search and many others. However, the process of retrieving relevant images is usually preceded by extracting some discriminating features that can best describe the database images. Therefore, the retrieval process is mainly dependent on comparing the captured features which depict the most important characteristics of images instead of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The feature matching procedure was based on the Canberra distance. A CBIR method was proposed in [8] by extracting both color and texture feature vectors using the discrete Wavelet transform and the Self Organizing Map (SOM) artificial neural networks. At query time, texture vectors were compared using a similarity measure of the Euclidean distance, and the most similar image was retrieved.…”
Section: -Related Workmentioning
confidence: 99%
“…The feature matching procedure was based on the Canberra distance. A CBIR method was proposed in [8] by extracting both color and texture feature vectors using the discrete Wavelet transform and the Self Organizing Map (SOM) artificial neural networks. At query time, texture vectors were compared using a similarity measure of the Euclidean distance, and the most similar image was retrieved.…”
Section: -Related Workmentioning
confidence: 99%
“…Some other studies use feature selection or dimensionality reduction in order to increase the performance of the classification and retrieval tasks. For example, Huneiti and Daoud 23 proposed a CBIR method by using the discrete wavelet transform (DWT) and the self organizing map (SOM) artificial neural networks. The results showed that the proposed method is more accurate than other methods that use only the texture features.…”
Section: Related Workmentioning
confidence: 99%
“…Paper have advantage of minimum searching time and maximum image retrieval results. In another work Huneiti et al [19] proposed the Discrete Wavelet Transform and Self Organizing Map (SOM) for efficient image retrieving. Retrieving mainly depends comparing of important features without comparing whole image features.…”
Section: Related Workmentioning
confidence: 99%